Kepemimpinan Hindu Dalam Geguritan Darma Kaya - I Wayan Semita (Kamaya: Jurnal Ilmu Agama, 2019)
The importance of applying the noble values ​​in the teachings of Hinduism, because to be a strong and disciplined generation is closely related to the souls of a strong leader and understanding of science both spiritual and physical knowledge, natural knowledge and religious knowledge Not only in ancient times ( the kingdom) the problem of leadership arises, in the present century the position of leader is seen as a more competitive arena, so that the process of achieving it seems to escape the theoretical order even to ethical and moral violations. The consequences of this method often produce figures that are not professional. So that its leadership cannot carry out its duties properly, but it actually causes misery for the people it leads. One of the gaguritan literature works that attracts attention is "Gaguritan Darmakaya". Gaguritan is still a rare text because until now it can only be found in writing on palm leaves found in the library of the Udayana University UNUD Literature Faculty of Denpasar and in the form of literacy and language transfer conducted by Ida Bagus Kade Raka from Grya Mas . Therefore in this study it was intended to highlight the gaguritan text from the concept of Hindu leadership. The problem faced is: if it is associated with the concept of Hindu leadership, how is the concept of Hindu leadership contained in Gaguritan Darmakaya?. The Hindu leadership in Gaguritan Darmakaya is: (a) the obligation to practice dharma, namely the obligation to do good and defend the truth; (b) the leader must be able to control himself, this enthusiasm is shown in Gaguritan Darmakaya with the teaching to understand oneself as a mirror unlike a container of water whose contents are empty so that the pelvis will shake it contains empty signs; (c) leaders must be intelligent, this is illustrated by the teachings of Rwa Bhineda as a teaching to solve problems and critical thinking to realize wisdom; (d) the leader can choose a friend, this teaching is proven by Darmakaya's search for (brother), and is encouraged to do good so that he does not regret later.